The phytochemical diversity and product quality of shea butter present confounding factors to product standardization in research - Masters, Eliot T. (International Journal of Basic & Clinical Pharmacology, 2018)
Muoghalu et al, describe the anti-inflammatory activity of whole unrefined shea butter in an animal model. This study is important because shea butter extracts have promising characteristics for treating inflammatory disorders. However, the authors did not appropriately characterise the concentration of the specific bioactive compounds identified from their literature review prior to their in vivo studies. This lack of characterisation limits ability to extrapolate the important anti-inflammatory findings more broadly.